Is Syariah Product Able to Be Go Viral by Not-Syariah Vlogger? - Haryanto, Budhi; Setiawan , Ahmad Ikhwan; Atina, Vivin Zulfa (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study aims to examine the moderating role of brand congruence and the mediating role of brand attitude of wardah beauty products. Data collection was carried out online to Muslim women aged 16-35 years who had never bought wardah products. Data collected from 280 respondents who watched the beauty vlogger's youtube video was then analyzed with partial least squares structural equation modelling (PLS-SEM). The results show that the credibility of beauty vlogers does not affect the desire to buy. However, product congruence and attitude affect the interest in buying wardah products. Furthermore, in the moderation test, it was found that product congruence did not moderate the relationship between credibility variables and buying interest. The mediation test found that brand attitudes partially mediated the relationship between attitude, attractiveness and expertise to purchase intent. The study also discusses its implications, both theoretical and practical, and its implications for future studies. Overall, it can be concluded that consumer interest in buying a cosmetic is based on the quality of the product, not from the credibility of the beauty vlogger.